2019
DOI: 10.1002/1873-3468.13703
|View full text |Cite
|
Sign up to set email alerts
|

Inducible knockout of ∆Np63 alters cell polarity and metabolism during pubertal mammary gland development

Abstract: The ∆Np63 isoform of the p53‐family transcription factor Trp63 is a key regulator of mammary epithelial stem cells that is involved in breast cancer development. To investigate the role of ∆Np63 at different stages of normal mammary gland development, we generated a ∆Np63‐inducible conditional knockout (cKO) mouse model. We demonstrate that the deletion of ∆Np63 at puberty results in depletion of mammary stem cell‐enriched basal cells, reduces expression of E‐cadherin and β‐catenin, and leads to a closed ducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…Our findings are in line with genetic lineage tracing experiments performed in salivary glands of adult mice showing that the transition of actively proliferating K14 + basal cells to both the ductal intercalated and excretory luminal cells of the gland occurs fairly quickly-within 14 days (Kwak et al, 2016;Kwak and Ghazizadeh, 2015). Moreover, the wide-spread defects observed upon the loss of DNp63 in the SG are also in good agreement with similar studies reported in the mammary gland (Forster et al, 2014;Kumar et al, 2019). Interestingly, conditional deletion of DNp63 in the pubertal mammary gland results in aberrant ductal formation presumably owing to altered stem cell differentiation (Kumar et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are in line with genetic lineage tracing experiments performed in salivary glands of adult mice showing that the transition of actively proliferating K14 + basal cells to both the ductal intercalated and excretory luminal cells of the gland occurs fairly quickly-within 14 days (Kwak et al, 2016;Kwak and Ghazizadeh, 2015). Moreover, the wide-spread defects observed upon the loss of DNp63 in the SG are also in good agreement with similar studies reported in the mammary gland (Forster et al, 2014;Kumar et al, 2019). Interestingly, conditional deletion of DNp63 in the pubertal mammary gland results in aberrant ductal formation presumably owing to altered stem cell differentiation (Kumar et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the wide-spread defects observed upon the loss of ΔNp63 in the SG are also in good agreement with similar studies reported in the mammary gland ( Forster et al., 2014 ; Kumar et al., 2019 ). Interestingly, conditional deletion of ΔNp63 in the pubertal mammary gland results in aberrant ductal formation presumably owing to altered stem cell differentiation ( Kumar et al., 2019 ). Moreover, ΔNp63 has also been shown to be important during pregnancy as ΔNp63KO mice showed defects in luminal progenitor cell proliferation and differentiation ( Forster et al., 2014 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous studies, myoepithelial cells were defined by the expression of basal compartment-biased genes Krt5, Cytokeratin 14 (Krt14), Cytokeratin 17 (Krt17), Acta2, Secreted Protein Acidic and Cysteine Rich (Sparc), Myosin light chain kinase (Mylk), Podoplanin (Pdpn) and C-X-C Motif Chemokine Ligand (Cxcl14) [15,22,26,[34][35][36]. Myoepithelial progenitor/stem cells were marked by the expression of genes previously shown to contribute to tissue reconstruction in fat pad transplantation assays and overall mammary developmental processes, such as Tumor protein p63 (Tp63) [37], Bromodomain PHD Finger Transcription Factor (Bptf) [17], and classical markers of mammary stem-like state, such as Leucine Rich Repeat Containing G Protein-Coupled Receptor 5 (Lgr5) [38], Neuregulin 1 (Nrg1) [39] and Inhibitor of DNA Binding 4, HLH Protein (Id4) [40] (Fig. 2B and Supplementary Fig.…”
Section: Improving the Classification Of Mammary Epithelial Cell Populationsmentioning
confidence: 99%